Judicial Activism - Pulido-Ortiz, Fabio Enrique (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
The objective of this paper is to improve the conceptual understanding of judicial activism. The work begins with the analysis of leading thesis of judicial activism highlighting its main explanatory weaknesses. Then, it is introduced the distinction between judicial activity, i.e the proper exercise of judicial powers, and judicial activism understood as a kind of improper exercise of judicial powers. The work concludes that judicial activism is a type of improper exercise of judicial powers which is characterized by the practice of judges to reconfigure power-conferring rules through their own judicial decisions.